2009
DOI: 10.1007/s00425-009-0897-3
|View full text |Cite
|
Sign up to set email alerts
|

The plasma membrane H+-ATPase is related to the development of salicylic acid-induced thermotolerance in pea leaves

Abstract: The plasma membrane H ?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 67 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…Plants quickly synthesized the hormone SA in response to environmental stress. A rapid increase in endogenous free-SA level was observed in plant thermotolerance (Dat et al 1998;Liu et al 2009b). SAG is a major metabolite conjugated form of SA.…”
Section: Sa Has Been Regarded As a Defense-related Plant Hormone In Ementioning
confidence: 96%
See 2 more Smart Citations
“…Plants quickly synthesized the hormone SA in response to environmental stress. A rapid increase in endogenous free-SA level was observed in plant thermotolerance (Dat et al 1998;Liu et al 2009b). SAG is a major metabolite conjugated form of SA.…”
Section: Sa Has Been Regarded As a Defense-related Plant Hormone In Ementioning
confidence: 96%
“…When tobacco mosaic virus (TMV)-inoculated tobacco leaves, the endogenously synthesized SA is primarily converted to SAG (Lee and Raskin 1998;Enyedi et al 1992;Malamy et al 1992). Liu et al (2009b) reported that SAG may act as a signal molecule as SA does involved pea thermotolerance induced by heat acclimation. Fig.…”
Section: Sa Has Been Regarded As a Defense-related Plant Hormone In Ementioning
confidence: 99%
See 1 more Smart Citation
“…A burst of free salicylic acid-induced thermotolerance at a temperature of 38±0.5ºC appeared subsequent to a change in both the activity and amount of PM H + -ATPase in pea leaves [5]. We assessed lupine cell H + -ATPase responses to different temperatures, which were close to optimal for plant growth in middle latitudes and Earth climate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key molecular players in cell homeostasis is plasmalemma H + -ATPase, which establishes a proton-electrochemical gradient across the plasma membrane, as well as the tonoplast H + -ATPase and H + -PPase, which are involved in such intricate physiological processes as intracellular pH regulation, cell elongation, and adaptation to different temperature stresses [3][4][5][6][7][8]. In our earlier work dealing with H + -ATPase activity and proton transport peculiarities in freezing-tolerant and non-tolerant genotypes of meadow fescue (Festuca pratensis Huds.…”
Section: Introductionmentioning
confidence: 99%